Neuroendoscopic Intervention for the Deep Midline Brain Tumors with Secondary Occlusive Hydrocephalus - Ulugbek M. Asadullaev (International Journal of Biomedicine, 2015)
This article analyzes the results of a clinical examination of 102 patients (78/76.47% men and 24/23.53% women) with a brain tumor (BT) complicated with a secondary obstructive hydrocephalus (SOH). All the patients were divided into 3 groups according to the type of surgery. Group I included 38(37.2%) patients who underwent Torkildsen's ventriculocisternostomy. Group II consisted of 34(33.3%) patients who underwent endoscopic third ventriculocisternostomy (ETV) with simultaneous endoscopic tumor removal. Group III included 30 (29.4%) patients who underwent a two-stage intervention: ETV in the first stage, and the endoscopic tumor removal in the second stage. The distinct advantages of EVT with tumor removal in the second stage of the operation were revealed.